1994
DOI: 10.1164/ajrccm.150.2.8049847
|View full text |Cite
|
Sign up to set email alerts
|

Fiberoptic bronchoscopy in brain-dead organ donors.

Abstract: Criteria for selecting lung donors include normal chest X-ray and adequate gas exchange, but normal bronchoscopy is not always required. Thus, we conducted a prospective study of fiberoptic bronchoscopy in 72 brain-dead donors scheduled for multiple organ procurement. Chest X-ray was considered normal in 37 donors (51%), and PaO2 was > 400 mm Hg with an FIO2 of 100% in 34 donors (47%). Fiberoptic bronchoscopy was normal in only 24 donors (33%). In the remaining 48 donors, inhalation of gastric contents (n = 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 12 publications
0
20
0
2
Order By: Relevance
“…In a study by Riou et al, fiberoptic bronchoscopy in brain-dead organ donors revealed inhalation of gastric contents in 36% [20]. A disadvantage of the use of gastric juice is the difficulty to standardize the injury model.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Riou et al, fiberoptic bronchoscopy in brain-dead organ donors revealed inhalation of gastric contents in 36% [20]. A disadvantage of the use of gastric juice is the difficulty to standardize the injury model.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the performance of a bronchoscopy, along with frequent pulmonary suction (respiratory physical therapy) and pulmonary expansion ventilation techniques (using PEEP), results in a significant increase in both the quality of the donor organs and in the number of transplantable organs (D) (29) (C). (56,(59)(60)(61)(62) A bronchoscopy can be performed either by a local hospital physician or by the transplant team surgeon (D). (28) During the bronchoscopy, respiratory fluids should be collected (bronchoalveolar lavage fluid) for Gram staining and cultures with the aim of guiding eventual antibiotic therapy (D).…”
Section: Lung Maintenancementioning
confidence: 99%
“…(6,29,57,63) Recommendations -A bronchoscopy is indicated for all potential lung donors (D) (29) (C). (56,(59)(60)(61)(62) Strong Recommendation. -If a bronchoscopy cannot be performed at the hospital of origin, clinicians should inform the team responsible for removing the organs that this test could not be performed.…”
Section: Lung Maintenancementioning
confidence: 99%
“…Este teste é um pré-requisito de diversas equipes de transplante pulmonar para aceitação de um órgão, especialmente quando há evidências de aspiração de conteúdo gástrico ou de infecção, uma vez que, como já foi dito, a presença de secreções purulentas usualmente contra-indica a utilização do órgão. Sua importância foi demonstrada por inúmeros estudos, dentre eles o conduzido por Riou et al 34 em que constataram que somente 33% dos doadores com morte cerebral e apenas 62% de todos os doadores considerados ideais apresentavam broncoscopia macroscopicamente sem alterações.…”
Section: Infecçãounclassified